The Long and Winding Road—Vestibular Efferent Anatomy in Mice - Lorincz, David; Poppi, Lauren A.; Holt, Joseph C.; Drury, Hannah R.; Lim, Rebecca; Brichta, Alan M. (Frontiers in Neural Circuits, 2022)
The precise functional role of the Efferent Vestibular System (EVS) is still unclear, but the auditory olivocochlear efferent system has served as a reasonable model of the effects of a cholinergic and peptidergic input on inner ear organs. However, it is important to appreciate the similarities and differences in structure of the two efferent systems, especially within the same animal model. Here, we examine the anatomy of the mouse EVS, from its central origin in the Efferent Vestibular Nucleus (EVN) of the brainstem, to its peripheral terminations in the vestibular organs, and we compare these findings to known mouse olivocochlear anatomy. Using transgenic mouse lines and two different tracing strategies, we examine central and peripheral anatomical patterning, as well as the anatomical pathway of EVS axons as they leave the mouse brainstem. We separately tag the left and right efferent vestibular nuclei (EVN) using Cre-dependent, adeno-associated virus (AAV)-mediated expression of fluorescent reporters to map their central trajectory and their peripheral terminal fields. We couple this with Fluro-Gold retrograde labelling to quantify the proportion of ipsi- and contralaterally projecting cholinergic efferent neurons. As in some other mammals, the mouse EVN comprises one group of neurons located dorsal to the facial genu, close to the vestibular nuclei complex (VNC). There is an average of just 55 EVN neurons with rich dendritic arborizations towards the VNC. The majority of EVN neurons, 55%, project to the contralateral eighth nerve, crossing the midline rostral to the EVN, and 32% project to the ipsilateral eighth nerve. The vestibular organs, therefore, receive bilateral EVN innervation, but without the distinctive zonal innervation patterns suggested in gerbil. Similar to gerbil, however, our data also suggest that individual EVN neurons do not project bilaterally in mice. Taken together, these data provide a detailed map of EVN neurons from the brainstem to the periphery and strong anatomical support for a dominant contralateral efferent innervation in mammals.